Nilai pendidikan islam dalam channel Gus Iqdam Official: Hybrid Dakwah - Innayah, Hanifah (PKBM DAARUL AHKAAM, 2024)
There are many ways to promote Islamic education. One option is to look at YouTube channels that are currently widely used. Gus Iqdam Official is known to provide content that contains Islamic educational values. The purpose of this study is to analyze Gus Iqdam's Islamic education values when preaching on online media. This research uses a qualitative approach method with descriptive analysis. The data source comes from several different videos on Gus Iqdam's official channel. In this research, the author uses the thematic method by using Nvivo software as a method and data analysis tool. Overall, the results of the analysis show that there are eight values of Islamic education as education in general public education, including: (i) Remembering Allah (ii) Sincerity (iii) Honesty (iv) Mutual Respect (v) Berahalqul Karimah (vi) Patience. The results of this study can be used as a description that can help in contemporary Islamic education so that da'wah can be carried out effectively and in accordance with applicable religious principles. The results of this study conclude that it is important to provide valuable information for da'i and Islamic education practitioners to take advantage of opportunities in the digital era and overcome the challenges that arise in order to transform Da'wah and the implementation of adaptive Islamic education in the midst of changing times.